Activation of SH2 domain-containing protein tyrosine phosphatase and inflammatory expression in psoriasis - Kieu Trang, Bui; Thi Kim Lien, Nguyen; Thi Xuan, Nguyen (Vietnam Journal of Biotechnology, 2022)
Psoriasis is a chronic autoimmune disease characterized by abnormal proliferation and differentiation of keratinocytes and infiltration of inflammatory cells into the site of inflammation. Plaque psoriasis is the most common type of psoriasis, affecting up to 80–90% of psoriasis cases. Among inflammatory cells, myeloid dendritic cells or Langerhans cells are mainly activated cells during the pathogenesis of psoriasis to induce activation and differentiation of naive T cells into T helper cells (Th)1 and Th17 cells. SH2 domain-containing protein tyrosine phosphatase (SHP) is a negative regulator of the phosphorylation of several proteins involved in cellular differentiation, growth and activation. Chronic inflammation promotes tumor progression, which is characterized by the release of carcinogenic antigens, including alpha-fetoprotein (AFP) and cancer antigen 125 (CA125) into blood and urine. They are common tumor markers to serve as predictors of cancer development and survival of cancer patients. To this end, blood samples of 103 psoriasis patients and 46 healthy subjects were collected. The mRNA expressions of SHP1 and SHP2 were examined by using quantitative RT-PCR and the serum levels of IL-6, TNF-α, IFN-γ, IL-17A, AFP and CA125 by ELISA. As a result, the mRNA level of SHP1 was higher expressed, whereas the level of SHP2 was unaltered in the patient group compared to the control individuals. Importantly, psoriasis patients had CA125 level higher than the clinical cutoff 35U/mL was 15.6%, while healthy individuals had CA125 level lower than 35U/mL. In addition, the serum TNF-α and IL-17A concentrations were significantly increased in the patient group. In conclusion, the results indicated the significant differences in expression of SHP1 gene and inflammatory response in psoriasis patients. This study further hint for investigations on the functional role of SHP1 in regulating activation of immune cells present in psoriasis patients.